Identification of Cattle Persistently Infected With BVDV (PI) By Ear-Notch Testing In Southeast of Iran - Mozaffari, Ali Asghar; Khalili, Mohammad; Jahangosha, Farzaneh (Animal Review, 2014)
Bovine viral diarrhea virus (BVDV) infection can induce a variety of economically important clinical manifestations in cattle herds. One potential outcome is the creation of calves that are viremic but immunotolerant to the virus. These persistently infected (PI) calves are the result of in utero exposure to BVDV prior to the development of a competent fetal immune system. The aim of this study was to detect of cattle persistently infected with BVDV by ear-notch testing in southeast of Iran. Ear-notch skin samples, 3 mm in diameter, were collected from a total of 127 cattle from 6 randomly selected herds (calves aged under 12 months ), using pliers usually used for ear tagging and skin notch sampling, as described by the manufacturer of the Herd check ELISA kit (IDEXX) for the detection of BVDV antigen in PI cattle. Overall, 0.78 per cent of the animals examined, were positive for BVDV antigen.This study identifies the cattle persistently infected with BVDV by ear-notch testing in southeast of Iran for the first time.